The Immunology - Ayurveda Perspective - Balakrishnan, Geethu; Shukla, Akhilesh (Current Traditional Medicine, 2024)
Introduction: Immunity can be defined as the ability of the human body to resist almost all types of organisms or toxins that tend to damage tissues and organs. Ayurveda, one of the oldest health sciences has its perspectives and practices on immunology delineated under the heads of Vyadhikshmatwa (tolerance against disease), Ojas (the quintessence of all bodily tissues that is responsible for natural bio-strength, vitality and immunity), Bala (strength), and Vikaravighata Bhavas (disease-resisting factors). Materials and Methods: For the present review, the materials were collected from the Ayurvedic literature, including the three major classical texts Brihatrayees Charaka Samhita, Sushruta Samhita, Ashtanga Samgraha and Ashtanga Hridaya, and their important commentaries by Chakrapani, Arunadutta, Hemadri, Indu, and Dalhana. Information from the current scientific literature, articles published in PubMed, and authentic webpages has also been incorporated into this study. Subsequently, an independent analysis of immunology from Ayurvedic classical texts is presented in this review. Discussion: Ayurvedic compendia have vividly described the perspectives and practices of immunity and the promotion of disease-resisting factors. In addition to being the repository of age-old medical practices and the treasure trove of herbal drugs, the immunomodulatory effects of these disease-resisting factors hold up even when bridging with new models based on modern science and technology. Conclusion: Rather than being a complementary science, Ayurveda is enriched with the concepts and practices of immunology. In order to free humanity from the grip of infections, it is important to explore the standalone and integrative aspects of science now.
Keywords: immunology